INTELLECTUAL CAPITAL IN THE ASSESSMENT OF BUSINESS VALUE - Yakobchuk, Valentyna; Malyk , Lyubov (Forestry, Forest, Paper and Woodworking Industry, 2012)
Presented in this paper are definitions of the following categories: intellectual property (IP), intellectual capital (IC), intangible assets (IA). An analysis of the assessment of intellectual capital in the value of Ukrainian and foreign companies has been made. Several approaches to improving the ways of the formation and assessment of intellectual capital have been proposed.